POLITICAL DISCOURSE AND POLITICAL COGNITION: AN ANALYSIS THROUGH THE LENS OF TEUN A. VAN DIJK (Modern education and development, 2025)
This article examines Teun A. van Dijk's analysis of the complex connection between political discourse and political cognition. It illuminates how political language influences political conduct and public opinion while illuminating the cognitive processes that underpin how political information is processed. Understanding the function of language in democratic processes and the ways in which cognitive biases can affect political communication are the two main goals of the study.